EFFECT OF CONFORMITY PEER AND ACCESS SITE AGAINST PORNOGRAPHY PREMARITAL SEXUAL BEHAVIOR OF YOUTH IN MAKASSAR - Bahar, Sabrina; Thalib, Tarmizi (Prosiding Seminar Nasional Riset Kuantitatif Terapan 2017, 2017)
The rise of adolescent premarital sexual behavior can give rise to unwanted pregnancy and HIV / AIDS. Adolescent premarital sexual behavior is a form of adolescent behavior that arise because of their sexual drive to the opposite sex without marriage. Premarital adolescent sexuality can be affected by conformity peers and access to pornographic sites. This research aims to determine the influence of peer conformity and access pornographic sites about premarital sexual behavior of teenagers in the city of Makassar. Subject of a study as a whole is 165 people. 195 test subjects and subjects 70 people.Methods of data analysis used in this study is a simple linear regression analysis test and regression correlation. The results of the study on the first hypothesis shows that there is influence of peer conformity with premarital sexual behavior of teenagers in the city of Makassar (r 2=0.058 and p=0.045). Results of research on both hypotheses suggests that there is influence access to pornographic sites with premarital sexual behavior of teenagers in the city of Makassar (r 2 = 0.405 and p=0.000). Results of research on the hypothesis that there are three simultaneous influence conformity peers and access to pornography sites about premarital sexual behavior of teenagers in the city of Makassar (r 2= 0.406 and p = 0.000). This paper illustrates that the higher the conformity peers and access to pornography sites, the higher the premarital sexual behavior. Writing is beneficial for relevant institutions as inputs, so it can take action to minimize the premarital sexual behavior in Makassar.Keywords— Premarital Sexual Behavior, Conformity Peers, Trusted Access Pornography, Youth.